SIMULATION OF OPTICAL PROPERTIES OF ZnO SUPERCELL BASED ON DENSITY FUNCTIONAL THORY. - Rezkallah, T. (University of Eloued جامعة الوادي, 2018)
This work presente the optical properties of ZnO semiconductor calculated by full potential linearized augmented plane wave (FP-LAPW) method with the local density approximation (LSDA) and the modified Becke-Johson (mBJ) potential. The scope of this work is to study some optical properties as (Dielctric function, Eloss Function, Refractive index …) of ZnO (1×1×1), (1×2×2) supercell in Zincblende (ZB) and Rocksalt (RS) phases. Our analysis revealed that the mBJ potential gives good results for the treatement of the d-orbitals.
Séminaire National Sur Laser Solaire Et Matériaux ElOeued 5-6 Février 2018
Keywords: Dielectric function, Refractive index, ZnO, mBJ, Supercell, FP-LAPW.